ANTESEDEN DAN KONSEKUENSI PENGKREASIAN NILAI WISATAWAN DOMESTIK DI INDONESIA BERBASIS PEMODELAN PLS-SEM - Devita Sari; Purwoko Purwoko; Fitroh Adhilla; Zunan Setiawan; Aftoni Sutanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study examines and analyzes the joy, love and positive surprise models, on consumers' intention to co-create value and visit. The research was conducted using an online survey which was distributed to the target respondents. Data analysis was carried out using PLS SEM through SMART PLS software Version 3.3.2. The findings of this study offer several interesting managerial implications, providing meaningful implications for business practitioners and destination marketers to drive tourist emotions and intentions to create shared value effectively. In particular, it will motivate travelers to engage more in conversations about the destination and stimulate their positive emotions, including joy, love and positive surprise. Such emotional states and experiences are likely to produce favorable responses as postulated by the SOR model. In addition, practitioners can also offer gifts to tourists who share useful information that helps other tourists to visit the destination.